2021
DOI: 10.1101/2021.05.07.21255988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic variant in SPDL1 reveals novel mechanism linking pulmonary fibrosis risk and cancer protection

Abstract: Idiopathic Pulmonary Fibrosis (IPF) is a rare disease with poor prognosis. By contrast, cancer is common in any elderly population and a leading killer, but is now often curable. Of note, whereas IPF is driven by cellular senescence, cancer is characterized by uncontrolled cell division. Using data available from two large biobank-based studies (Finnish FinnGen study and UK biobank), we conducted a comprehensive analysis of the shared genetic background of IPF and cancer. In a population sample of 218,792 Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…One such new observation is a missense variant (p.Arg20Gln; AF = 3%, gnomAD NFSEE = 0.7%) in SPDL1 with a pleiotropic association. It is associated with a strongly increased risk of idiopathic pulmonary fibrosis (OR = 3.1, P = 1.0 × 10 −15 ) but protective with an end point that combines all cancers (OR = 0.82, P = 2.1 × 10 −15 ) 32 . Other associations between variants and disease described in separate manuscripts include the following: an inframe deletion in MFGE8 and coronary atherosclerosis (p.Asn239dup; AF = 2.9%, gnomAD NFSEE = 0%, OR = 0.74, P = 5.4 × 10 −15 ) 33 ; a frameshift variant in MEPE (p.Lys101IlefsTer26; AF = 0.3%, gnomAD NFSEE = 0.07%, OR = 18.9, P = 1.5 × 10 −11 ) and otosclerosis 34 ; and a missense variant in ANGPTL7 (p.Arg220Cys; AF = 4.2%, gnomAD NFSEE = 0.06%, OR = 0.7, P = 7.2 × 10 −16 ) and glaucoma 35 .…”
Section: New Disease Associationsmentioning
confidence: 99%
“…One such new observation is a missense variant (p.Arg20Gln; AF = 3%, gnomAD NFSEE = 0.7%) in SPDL1 with a pleiotropic association. It is associated with a strongly increased risk of idiopathic pulmonary fibrosis (OR = 3.1, P = 1.0 × 10 −15 ) but protective with an end point that combines all cancers (OR = 0.82, P = 2.1 × 10 −15 ) 32 . Other associations between variants and disease described in separate manuscripts include the following: an inframe deletion in MFGE8 and coronary atherosclerosis (p.Asn239dup; AF = 2.9%, gnomAD NFSEE = 0%, OR = 0.74, P = 5.4 × 10 −15 ) 33 ; a frameshift variant in MEPE (p.Lys101IlefsTer26; AF = 0.3%, gnomAD NFSEE = 0.07%, OR = 18.9, P = 1.5 × 10 −11 ) and otosclerosis 34 ; and a missense variant in ANGPTL7 (p.Arg220Cys; AF = 4.2%, gnomAD NFSEE = 0.06%, OR = 0.7, P = 7.2 × 10 −16 ) and glaucoma 35 .…”
Section: New Disease Associationsmentioning
confidence: 99%
“…In 15/23 non-suspicious loci harboring a nonsynonymous variant, the nonsynonymous variant had the highest PIP. These included known missense variants such as rs116483731 (p.Arg20Gln) in SPDL1 for idiopathic pulmonary fibrosis (IPF) 61,62 and rs28929474 (p.Glu366Lys) in SERPINA1 for chronic obstructive pulmonary disease (COPD) 63,64 . In addition, we observed successful fine-mapping in 2 novel loci for asthma, i) rs41286560 (p.Pro558Thr) in RTL1 , a missense variant known for decreasing height 65,66 and ii) rs34187696 (p.Gly337Val) in ZSCAN5A , a known missense variant for increasing monocyte count 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Fine-mapping suggested deleterious coding causal variants at three loci. In addition to the previously reported coding variants in TERT and SPDL1 4,6 , fine-mapping identified a coding variant in KIF15 (predicted missense, rs138043992, AF = 0.29%, OR[95% CI] = 1.71[1.39-2.10], PIP = 0.24), enriched 2.6-fold in the Finnish population compared to non-Finnish non-Estonian Europeans (NFEE, gnomAD v2.1.1) and predicted as probably damaging by Polyphen and deleterious by SIFT.…”
Section: Fine-mapping In the Finnish Population Suggests Missense Variant To Be Causal At Kif15mentioning
confidence: 85%
“…As IPF has, by definition, no identifiable cause, genome-wide approaches are especially attractive as they may provide insight into underlying causes, pathogenesis, and might potentially reveal novel therapeutic avenues. Genome-wide association studies (GWAS) of IPF have thus far reported at least 23 associated loci [2][3][4][5][6][7][8][9][10][11] highlighting genes involved with telomere maintenance 12 , cell adhesion, airway clearance, and innate immunity. These studies have mainly been restricted to individuals of European descent and common variants, and have identified few associations to conclusively functional variants.…”
Section: Introductionmentioning
confidence: 99%